Intraventricular monitoring for temporal lobe epilepsy: report on technique and initial results in eight patients. Issue 5 (1st May 2003) - Song, J K; Abou-Khalil, B; Konrad, P E
Abstract : Objective and importance: Resective surgery is an effective treatment for refractory temporal lobe epilepsy. In difficult cases, invasive monitoring may be needed to precisely lateralise and localise seizure foci of mesial temporal origin. The authors present a modified technique for image guided, endoscopic placement of an intraventricular electrode array (IVE) that abuts the amygdalo-hippocampal complex. Methods: Eight patients with suspected mesial temporal lobe epilepsy had placement of an IVE in conjunction with other invasive electrodes. Seven of these patients also had subdural grid or strip electrodes and four had foramen ovale electrodes. Frameless image guidance was used to place a custom 10-contact depth electrode through a rigid neuroendoscope within the atrium of the lateral ventricle. Once proper orientation towards the temporal horn was confirmed, the IVE array was advanced into the temporal horn to the temporal tip. The endoscope was removed and electrode placement was confirmed through an intraoperative lateral skull radiograph and on visual inspection at the time of resection in two cases. Results: The IVE was crucial for localisation in one patient and helped localisation in four others. Surgery was offered to seven patients. The only serious complication of IVE placement was a thalamic contusion presumably from an errant electrode tip. One electrode was inadvertently placed into the frontal horn. There were no deaths and no permanent morbidity associated with the procedure. Conclusion: Endoscopically placed temporal horn, intraventricular electrodes provide an alternative to transcortical depth electrode placement. The technique hopefully can avoid complications associated with multiple depth electrode placements, especially when bilateral amygdalo-hippocampal electrical recordings are desired, although there may be a steep learning curve.